Innovatsionnye tekhnologii: Metodologiya, obychenie i sovershenstvovanie ratsionalnoj sistemy dvigatelnykh dejstvij v sprinterskom bege - Vlassov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The research carried out by the author has allowed to define the basis of the technique of the track and field athletics exercises, having the invariant character. The basis of the rational technique of the track and field athletics exercises is the uniform, common for all categories and levels of the physical preparedness of all engaged in running, jumps and throwings. Thus, uncertainty of understanding of the basis of the technique of the track and field athletics exercises at the initial stages of the training and ways of its perfection is eliminated; the prospect of the retraining to the more "perfect" technique of motor actions disappears. The essence of the algorithm of the key actions during the running as the formula of self-checking in the opinion of the author consists in the following: 1. In the optimum width of foots statement on a support. 2. In the "rake-picking up" character of the fast pushing away by the front part of foots. 3. In the coordinated acceleration of the counter movements of hands and legs. The presented managing algorithm of the key actions in the sprint running as the formula of self-checking was applied on trainings with students. The analysis of results of the research has shown the increased cognitive-motor activity of students in the educational tasks, the improvement of the running rhythm, the increase of speed, the formation of the objectively individualized technique of the sprint running.